1984
DOI: 10.1095/biolreprod31.4.785
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Human Sertoli Cell Population: Its Distribution, Relation to Germ Cell Numbers, and Age-Related Decline 1

Abstract: The human Sertoli cell population was characterized in 14 men by histometric analysis and by direct counts of nuclei in testicular homogenates. Testes obtained at autopsy were perfused with glutaraldehyde and embedded in Epon. Nucleolar and nuclear volumes were determined by the formula of a sphere given the diameter of the nucleoli or average diameter of nuclei measured at the height and width. Nuclear volume was also estimated by adding volumes of nuclear profiles in 0.5-micron serial sections. Sertoli cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(118 citation statements)
references
References 22 publications
7
106
2
Order By: Relevance
“…Observations in humans with one of the described gene defects, impairing FSH action (4-6) also suggest that FSH is required for the development of the Sertoli cell population. The number of Sertoli cells is directly associated with sperm-producing capacity, since each of these somatic cells can nurture only a limited number of developing spermatogenetic cells (7). In agreement with these findings, men with idiopathic HH (IHH) and lack of prior endogenous puberty display poor response to pulsatile GnRH in terms of testicular growth and spermatogenesis (8).…”
Section: Introductionmentioning
confidence: 58%
“…Observations in humans with one of the described gene defects, impairing FSH action (4-6) also suggest that FSH is required for the development of the Sertoli cell population. The number of Sertoli cells is directly associated with sperm-producing capacity, since each of these somatic cells can nurture only a limited number of developing spermatogenetic cells (7). In agreement with these findings, men with idiopathic HH (IHH) and lack of prior endogenous puberty display poor response to pulsatile GnRH in terms of testicular growth and spermatogenesis (8).…”
Section: Introductionmentioning
confidence: 58%
“…Therefore, in our group of infertile men with normal FSH levels and high endogenous testosterone concentrations, it is tempting to evoke the absence and or presence of unfunctional specific receptors especially for estrogen in the proximal caput epididymis. According to Matsumoto et al [29], we should have quantitatively a normal spermatogenesis in these patients; nevertheless, the number of Sertoli cells is important to consider and a good correlation between the sperm production and that parameter has been reported [23]. Besides the immunological FSH value, the biopotency of FSH should be also taken into account as well as the presence of IgG antibodies [16,22,46,48].…”
Section: Discussionmentioning
confidence: 95%
“…It is then most probable that the Sertoli cells in the contralateral scrotal testes of the cryptorchid bucks are more efficient in supporting spermatogenesis. It has been reported that spermatid -Sertoli cell ratio is the determinant of the workload and function of the Sertoli cell [19] and spermatogenic efficiency [12]. The spermatid-Sertoli cell ratio is an important marker of spermatogenesis as it has been demonstrated that relative changes in daily sperm production would adjust the number of spermatids supported by the Sertoli cell population [27].…”
Section: Discussionmentioning
confidence: 99%